Resíduos de bifenilos policlorados em arroz e feijão do estado do Rio Grande do Sul - Cocco, Roberta (2011)
Polychlorinated biphenyls (PCBs) were commercially produced between 1929 and the mid 1980s with industrial purposes. The same properties that interested industrially, as chemical inertness, high dielectric constant, resistance to burning; were also responsible for the spreading of the PCBs in all of the environmental compartments, mainly due to the inadequate discard of equipments that contained PCBs (electronics), contaminating the water and the soil. They are persistent and non-biodegradable compounds that get accumulated in the environment, influencing all of the organisms in the food chain, and consequently all the food that is part of this chain. Human exposure to PCBs is the result of the large consumption of contaminated food, and also by inhalation and dermal absorption in hazardous environments, being the ingestion by contaminated food the main route of exposure. From conducted studies, its harmful effects to humans were found. Cereals and legumes deserve special attention in our diet, because, besides being essential food of easy acquisition, they are part of the general population s daily diet. Among these, rice and beans. For this reason, and because of the existence of environmental contamination by PCBs, it becomes of great interest to detect polychlorinated biphenyl residues in these foods. Because of this, combined with the persistence of the PCBs and their maleficent effects to humans, the general aim of this study was to identify and quantify indicator PCB residues in rice and bean samples obtained of the state of Rio Grande do Sul, in the year 2010. It is also intended to calculate the estimated daily ingestion of PCB residues from the contamination existing in rice and beans, and determination of fat content to correlate with levels of PCBs. The determination of the PCB residues was performed by gas chromatograph coupled to mass spectrometry (GC-MS), in the electron impact mode, after the extraction of the compound through the QuEChERS method. In the rice samples, average values of 0,05 ng g-1 for the PCB 28, 0,67 ng g-1 for the PCB 52, 0,24 ng g-1 for the PCB 101, 0,27 ng g-1 for the PCB 118, 1,28 ng g-1 for the PCB 138, 1,43 ng g-1 for the PCB 153 and 0,45 ng g-1 for the PCB 180. The PCB 52 was the most frequent, being found in 72,7% of the rice samples, followed by the PCBs 153 (54,5%), 138 (50,0%), 101 and 180 (13,6%), 118 (9,0%) and 28 (0,0%). In the beans samples, average values of 0,14 ng g-1 were found for the PCB 52, 1,63 ng g-1 for the PCB 101, 1,33 ng g-1 for the PCB 118, 0,92 ng g-1 for the PCB 138 and 0,05 ng g-1 for the PCBs 28, 153 and 180. The PCB 118 was the most frequent, being detected in 22,2% of the beans samples, followed by the PCBs 138 (11,0%), 52 and 101 (5,5%), and 28, 153 and 180 (0,0%). It was also observed that rice presented higher PCB average levels than beans. The estimated daily intake of PCBs, this was 7.82 ng kg-1 and 3.14 ng kg-1 body weight per day, for rice and beans, respectively. In relation to the percentage of fat rice had a fat content of 0.32% and 1.10% for beans. However, it is extremely important studies of this nature, because through this research it was concluded that there are still PCB residues in food of Rio Grande do Sul.